El protocolo de kyoto: ¿una oportunidad para la industria colombiana? - Monroy, Néstor; Aguirre, Alejandro (Revista de Ingeniería, 2003)
Knowing the Kyoto Protocol is a huge opportunity for the Colombian industry to be more competitive. Although there are restrictions, in the future the CO2 market can make a difference for many companies in the environmental, economic, social and competitiveness issues. However, there are determinant factors like prices, subsidies and legislation that influence the viability and risks of a project, according to their development. This article explores the perspectives and impacts of this market in the industry by analyzing a specific case in a beer plant.